Modulation impact of Diazinon forms on gene expression profile and DNA damage pathway in male mice - Neama I. Ali, Lamiaa M. Salem, Sawsan Y. Elateek, Wagdy K. B. Khalil (Journal of Applied Pharmaceutical Science, 2020)
Diazinon (DZN) is an organophosphate pesticide used widely in agriculture. Unexpectedly, the pure pesticide compounds are less toxic than its commercial formulations. Therefore, the present study aimed to compare the commercial DZN formulation Basudin 60EM® and active ingredients forms of DZN to find the nontoxic form. Several groups of male mice were treated with different doses (1/40, 1/20, and 1/10 of LD50) of commercial formulation and active ingredients of DZN pesticide for 4 weeks. A quantitative Real-Time PCR (RT-PCR) was conducted to investigate the expression of TNF-α, p53, and Caspase-3 genes. Furthermore, the effect of both forms of DZN on intracellular Reactive Oxygen Species (ROS) generation and DNA damage was studied. The results showed that the TNF-α, p53, and Caspase-3 expression levels were increased in commercial formulation-treated mice than those treated with active ingredient form. Moreover, the commercial formulation form was able to increase ROS generation and induce DNA damage much more than the active ingredient-treated mice. The results concluded that not only the organophosphates but also the other byproducts affect the cellular responses to cytokine and apoptotic elements through alteration in the mRNA expression by increasing the levels of free radical generation.
Keywords: Diazinon, apoptosis, ROS formation, DNA damage, gene expression.